ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI YANG EFISIEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Desinta Natalia Siregar; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of financial reporting quality, debt maturity, conservatism, board of commissioners effectiveness, audit committee effectiveness, and institutional ownership on investment efficiency.The population of this study were the manufacturing company listed on the Indonesia Stock Exchange in the period of 2017-2019. Based on the purposive sampling method, the final sample obtained 327 data. Multiple linear regression was used to test the hypothesis in this study.The study reveals that financial reporting quality and conservatism have a significant effect on investment efficiency, whereas debt maturity have a negative and significant effect on investment efficiency. In addition, the effectiveness of the board of commissioners, the effectiveness of the audit committee, and institutional ownership have no effect on investment efficiency.